2021
DOI: 10.32604/cmes.2021.016416
|View full text |Cite
|
Sign up to set email alerts
|

BEVGGC: Biogeography-Based Optimization Expert-VGG for Diagnosis COVID-19 via Chest X-ray Images

Abstract: coronavirus disease has caused more than 2 million deaths worldwide. Mainly diagnostic methods of COVID-19 are: (i) nucleic acid testing. This method requires high requirements on the sample testing environment. When collecting samples, staff are in a susceptible environment, which increases the risk of infection. (ii) chest computed tomography. The cost of it is high and some radiation in the scan process. (iii) chest X-ray images. It has the advantages of fast imaging, higher spatial recognition than chest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Pham et al [19] proposed a supervised multi-label classification framework based on CNN, which uses the hierarchical dependence between abnormal labels to improve the diagnosis accuracy of chest Xray images. Sun et al [20] proposed a novel framework of BEVGG for diagnosing COVID-19 through chest X-ray images and used a biogeography-based optimization method to optimize hyperparameter values of convolutional neural networks, and the experimental results showed that the framework performs higher than the current methods. Gayathri et al [21] proposed a computer-assisted diagnosis method using chest X-ray images, sparse autoloader, and feedforward neural network FFNN, which reached high results in diagnosing COVID-19.…”
Section: Related Work 21 Convolutional Neural Network Based Pneumonia...mentioning
confidence: 99%
“…Pham et al [19] proposed a supervised multi-label classification framework based on CNN, which uses the hierarchical dependence between abnormal labels to improve the diagnosis accuracy of chest Xray images. Sun et al [20] proposed a novel framework of BEVGG for diagnosing COVID-19 through chest X-ray images and used a biogeography-based optimization method to optimize hyperparameter values of convolutional neural networks, and the experimental results showed that the framework performs higher than the current methods. Gayathri et al [21] proposed a computer-assisted diagnosis method using chest X-ray images, sparse autoloader, and feedforward neural network FFNN, which reached high results in diagnosing COVID-19.…”
Section: Related Work 21 Convolutional Neural Network Based Pneumonia...mentioning
confidence: 99%
“…The sixth paper "BEVGGC: Biogeography-Based Optimization Expert-VGG for Diagnosis COVID-19 via Chest X-ray Images" by Sun et al [6]. They proposed a novel framework-BEVGG and three methods (BEVGGC-I, BEVGGC-II, and BEVGGC-III) to diagnose COVID-19 via chest X-ray images.…”
mentioning
confidence: 99%